Nine years of project‐based learning in engineering - Oliveira, José Manuel Nunes (2012)
The engineering programmes offered at the Higher Education Polytechnic School of Águeda, University of Aveiro, have been organised, since 2001, around the Project Based Learning paradigm. This paper will briefly set the scene for the educational development and will then proceed to describe the curricula implementation that is nowadays on the field, reflecting the accumulated nine-years’ experience of running the programmes. Finally, the author will offer his personal perspective on the difficulties of the development and its implementation, as an actor engaged in the process.